The Effect of Fashion Involvement and Hedonic Shopping Values on Fashion Impulse Buying in Aceh: The Mediating Role of Positive Emotions - Mariyudi; Nurainun; Heriyana; Sapna Biby; Irvan (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The fashion industry in Indonesia continues to grow, including in Aceh, where rising consumer interest in fashion products has been accompanied by an increase in impulse buying behavior. Understanding the factors that drive this behavior is important to explain why Aceh represents a relevant research context.Purpose: This study aims to examine the effects of fashion involvement and hedonic shopping value on impulse buying decisions, with positive emotions as a mediating variable.Design/Method/Approach: This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 152 respondents in Aceh using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS software.Findings/Results: The results indicate that fashion involvement and hedonic shopping values have positive effects on impulse buying. Positive emotions significantly mediate both relationships.Conclusion: The findings suggest that fashion marketers should design strategies that stimulate positive emotions to encourage impulse purchases. Such strategies are expected to be particularly effective among consumers with higher levels of fashion involvement, who tend to exhibit stronger purchasing tendencies.Originality/Value (State of the Art): This study contributes to the literature on consumer behavior in the fashion sector by highlighting the mediating role of positive emotions in impulse buying behavior. It also offers practical insights for marketers in developing more effective promotional strategies. Keywords: fashion involvement, hedonic shopping value, impulse buying, positive emotions, fashion marketers